2002
DOI: 10.1095/biolreprod66.6.1790
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fertilin and CD9 in Bovine Trophoblast and Endometrium During Implantation1

Abstract: The superficial placentation of cattle involves the development of fetal binucleate cells that arise from the chorion and migrate between adjacent cell tight junctions to fuse with maternal epithelium. Thus, the temporal and spatial patterns of expression of the cell migration, adhesion, and fusion molecules fertilin and CD9 were investigated in bovine trophoblast and endometrium. Bovine fertilin alpha and fertilin beta messenger RNA sequences were amplified by reverse transcriptase-polymerase chain reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The expression of CSH1 has been confirmed in the embryo before its attachment to endometrium, however, the spatial (subcellular) localization of CSH1 protein within the TGC has not been shown (Kessler et al 1991. Furthermore, CD9, a cell-surface protein implicated in cell adhesion, differentiation, and migration, is expressed in the BNC and may participate in the fusion of trophoblast cells and endometrial epithelia (Xiang & MacLaren 2002, Liu et al 2006. Therefore, the appearance of TGCs during this critical transitional stage and the TGCs' ability to produce factors, CSH1 and CD9, which enable conceptus:maternal interaction highlight the importance of this differentiated trophoblast cell type.…”
Section: Blastocyst Elongation and Differentiationmentioning
confidence: 99%
“…The expression of CSH1 has been confirmed in the embryo before its attachment to endometrium, however, the spatial (subcellular) localization of CSH1 protein within the TGC has not been shown (Kessler et al 1991. Furthermore, CD9, a cell-surface protein implicated in cell adhesion, differentiation, and migration, is expressed in the BNC and may participate in the fusion of trophoblast cells and endometrial epithelia (Xiang & MacLaren 2002, Liu et al 2006. Therefore, the appearance of TGCs during this critical transitional stage and the TGCs' ability to produce factors, CSH1 and CD9, which enable conceptus:maternal interaction highlight the importance of this differentiated trophoblast cell type.…”
Section: Blastocyst Elongation and Differentiationmentioning
confidence: 99%
“…Many clinical studies have revealed that reduced CD9 expression is associated with a poor prognosis in various cancers, including non-small-cell lung cancers, breast cancers, and colon cancers (Huang et al 1998, Funakoshi et al 2003, Hashida et al 2003. Although originally identified as a surface antigen on a pre-B cell line (Kersey et al 1981), CD9 is also expressed on blastocysts in mice and endometrium epithelial cells in human and cattle (Le Naour et al 2000, Park et al 2000, Xiang & MacLaren 2002. Given the striking similarities between embryogenesis and the biology of cancer cells, especially in the process of the invasion, CD9 might be involved in embryo-invasive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This fusion competence could be restored upon injection of mRNA from either human or mouse CD9 into CD9 -/-mouse oocytes [6]. In addition, CD9 is expressed in pig oocytes during early growth and meiotic maturation and that it participates in sperm-oocyte interactions during fertilization [5].Apart from the expression of CD9 on the plasma membrane of oocytes in the mouse [2-4, 6] and pig [5] , it is also localized to the oocyte microvillar membrane [7] , blastocysts in mouse [3,8], and endometrium epithelial cells in the mouse [9], human [10] and bovine [11] . Accordingly, CD9 is required for normal microvillar shape and distribution in the mouse [7] and plays a role in inhibiting embryo implantation [8].…”
mentioning
confidence: 99%
“…CD9 expression in the uterus is upregulated in an ovarian steroid hormone-dependent manner, implicating multiple roles of CD9 in regulation of embryo implantation during the peri-implantation period [9]. At the same time, CD9 is involved in bovine binucleate cell migration and fusion in the trophoblast and endometrium [11].It is unclear whether CD9 is expressed on the plasma membrane of oocytes in bovine and what role CD9 plays in sperm-oocyte interaction. To fill in the gap in knowledge that furthers understanding of tetraspanin CD9 in bovine oocytes and its role in fertilization, in the present study, we examined (1) whether CD9 is located in bovine oocytes and (2) whether CD9 is involved in sperm-oocyte interaction during fertilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation